Glue solution, glue solution preparation method and method for manufacturing halogen-free high-Tg copper-clad plate

By using a specific proportion of modified epoxy resin and inorganic fillers in the copper covering fluid, the problem of insufficient thermal heat resistance of the existing copper -covering plate was solved, and the preparation of high -performance halogen -free high TG copper -covering plates was realized to meet the high -end market. need.

CN119371819AInactive Publication Date: 2025-01-28宁波甬强科技有限公司

Patent Information

Application Number
CN202411449437.3
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-10-17
Publication Date
2025-01-28
Estimated Expiration
Not applicable · inactive patent

AI Technical Summary

Technical Problem

The existing copper clad plate has poor comprehensive performance and insufficient heat resistance, which is unable to adapt to high-end market demand.

Method used

Provides a rubber fluid that includes polyurethane modified epoxy resin, benzene pinopizide resin, phosphorus -containing epoxy resin, modified phenolic epoxy resin, multi -functional epoxy resin, inorganic fillers, curing agent, catalyst, additive, and additives, additives, and additives and additives and additives and additives. Organic solvents, through specific proportion and preparation methods, form a high -performance halogen -free high Tg copper plate.

Benefits of technology

It improves the heat resistance, toughness, glassization transformation temperature, flame retardant performance, mechanical performance and heat resistance impact effect of the material, and meet the complex and harsh PCB lead -free process requirements.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119371819A_ABST
    Figure CN119371819A_ABST
Patent Text Reader

Abstract

The glue solution is prepared from the following components in parts by weight: 30 to 50 parts of polyurethane modified epoxy resin, 40 to 100 parts of benzoxazine resin, 60 to 90 parts of phosphorus-containing epoxy resin, 30 to 50 parts of modified novolac epoxy resin, 30 to 50 parts of multifunctional epoxy resin, 30 to 60 parts of inorganic filler, 5 to 10 parts of curing agent, 0.5 to 5 parts of catalyst, 3 to 8 parts of auxiliary agent and 50 to 80 parts of organic solvent. The glue solution provided by the invention has good heat resistance, toughness, glass transition temperature, flame retardant property, mechanical property, thermal shock resistance and thermal expansion coefficient. The invention also discloses a preparation method of the glue solution and a method for manufacturing the halogen-free high-Tg copper-clad plate.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to a copper clad laminate manufacturing technology, and in particular to a glue solution, a glue solution preparation method and a method for manufacturing a halogen-free high-Tg copper clad laminate. Background Art

[0002] Copper Clad Laminate (CCL) is the main material for manufacturing printed circuit boards (PCBs), and is therefore an indispensable basic electronic material for any electronic product. With the rapid development of the PCB industry, the market demand for high-performance copper clad laminates is increasing. Since its comprehensive development in the lead-free era, the product's heat resistance, glass transition temperature (Tg) value, thermal expansion coefficient (CTE value), PCB processability and other properties have received special attention. The balanced development of copper clad laminate substrate performance has become an important development trend in the development of new copper clad laminate materials.

[0003] The current demand for electronic products to be light, thin, short, small and digital, miniaturization, multi-function, high performance and high reliability have become the mainstream development direction. Therefore, PCB design is moving towards high multi-layer, fine graphics and high density. The requirements for line width, line spacing, aperture, hole wall and other processes in the PCB industry are also gradually moving towards high integration, high density and high multi-layer. For example, the mainstream high-density interconnect laminate (HDI) requires its micro-via aperture to be less than 6mil, the micro-via ring diameter to be less than 0.35mm, the contact density to be more than 130in / m2, the wiring density to be more than 117in / m2, and the line width / line spacing to be less than 0.1mm / 0.1mm. High-level HDI (more than twelve layers) needs to withstand special processes such as high-level multiple hot pressing and more precise and detailed process requirements. With the development of high-density mounting technology, especially the full implementation of lead-free and the rapid development of surface mount technology (SMT), the number of times and temperatures that materials are repeatedly subjected to thermal shock during PCB processing and installation of complete machine accessories are higher than traditional requirements. All of this ultimately translates into a huge challenge to the reliability of high-performance copper clad laminates.

[0004] The existing copper clad laminates have poor overall performance and insufficient heat resistance, which makes them unable to meet the needs of the high-end market. Summary of the invention

[0005] The technical problem to be solved by the present invention is to provide a glue having good heat resistance, toughness, glass transition temperature, flame retardancy, mechanical properties, heat shock resistance and thermal expansion coefficient.

[0006] In order to solve the above technical problems, the glue provided by the present invention comprises the following components in parts by weight: 30-50 parts of polyurethane modified epoxy resin, 40-100 parts of benzoxazine resin, 60-90 parts of phosphorus-containing epoxy resin, 30-50 parts of modified phenolic epoxy resin, 30-50 parts of multifunctional epoxy resin, 30-60 parts of inorganic filler, 5-10 parts of curing agent, 0.5-5 parts of catalyst, 3-8 parts of auxiliary agent and 50-80 parts of organic solvent.

[0007] Preferably, the glue contains the following components in parts by weight: 30-50 parts of polyurethane modified epoxy resin, 50-80 parts of benzoxazine resin, 60-80 parts of phosphorus modified epoxy resin, 30-50 parts of modified phenolic epoxy resin, 30-50 parts of multifunctional epoxy resin, 30-60 parts of inorganic filler, 5-10 parts of curing agent, 0.5-5 parts of catalyst, 3-8 parts of auxiliary agent and 50-80 parts of organic solvent.

[0008] Preferably, the adhesive contains the following components in parts by weight: 30 parts of polyurethane modified epoxy resin, 70 parts of benzoxazine resin, 60 parts of phosphorus modified epoxy resin, 45 parts of modified phenolic epoxy resin, 30 parts of multifunctional epoxy resin, 55 parts of inorganic filler, 8 parts of curing agent, 1.5 parts of catalyst, 3 parts of auxiliary agent and 60 parts of organic solvent.

[0009] Preferably, the adhesive contains the following components in parts by weight: 40 parts of polyurethane modified epoxy resin, 65 parts of benzoxazine resin, 65 parts of phosphorus modified epoxy resin, 30 parts of modified phenolic epoxy resin, 35 parts of multifunctional epoxy resin, 40 parts of inorganic filler, 8 parts of curing agent, 0.9 parts of catalyst, 4 parts of auxiliary agent and 70 parts of organic solvent.

[0010] Preferably, the adhesive contains the following components in parts by weight: 45 parts of polyurethane modified epoxy resin, 55 parts of benzoxazine resin, 60 parts of phosphorus modified epoxy resin, 40 parts of modified phenolic epoxy resin, 30 parts of multifunctional epoxy resin, 55 parts of inorganic filler, 7 parts of curing agent, 1.2 parts of catalyst, 5 parts of auxiliary agent and 65 parts of organic solvent.

[0011] Preferably, the organic solvent is a mixture of any one or more of DMF, acetone, butanone, methyl butanone, cyclohexanone, propylene glycol methyl ether, toluene, xylene, ethylene glycol methyl ether, ethylene glycol ethyl ether, ethylene glycol butyl ether, methanol, isopropanol, propylene oxide, and cyclohexane;

[0012] The modified benzoxazine resin is a mixture of any one or more of phenylmethane modified benzoxazine resin, double bond modified benzoxazine resin, and bisphenol A type epoxy modified benzoxazine resin;

[0013] The phosphorus-containing epoxy resin is a mixture of any one or more of DOPO-type modified epoxy resin, DOPO-HQ-type modified epoxy resin, DOPO-NQ-type modified epoxy resin, etc.;

[0014] The modified novolac epoxy resin is a mixture of any one or more of bisphenol A novolac epoxy resin, o-cresol novolac epoxy resin, and BPA novolac epoxy resin;

[0015] The multifunctional epoxy resin is a mixture of any one or more of a trifunctional epoxy resin and a tetrafunctional epoxy resin;

[0016] The inorganic filler is a mixture of two or more of silicon micropowder, aluminum oxide, zinc oxide, magnesium hydroxide, aluminum hydroxide, barium sulfate, silicon nitride, boron nitride, and talc;

[0017] The auxiliary agent is a mixture of any one or more of an organic silane coupling agent, a titanate ester, and an aluminate coupling agent;

[0018] The curing agent is a mixture of any one or more of 4,4'-dioxydiphenyl sulfone, dicyandiamide, and phosphorus-containing phenolic curing agent;

[0019] The catalyst is a mixture of any one or more of imidazole, 2-methylimidazole, 2-ethylimidazole, 2-phenylimidazole, 2-ethyl-4-methylimidazole, 2-ethyl-4-phenylimidazole and boric acid.

[0020] In order to solve the above technical problems, the present invention provides a method for preparing the glue solution, comprising the following steps:

[0021] S1. Stir an organic solvent, a polyurethane-modified epoxy resin, a benzoxazine resin, a phosphorus-modified epoxy resin, a modified phenolic epoxy resin and a multifunctional epoxy resin for 2-3 hours until the epoxy resin is completely dissolved in the organic solvent;

[0022] S2. Add inorganic fillers and additives, and pass through a homogenizer to homogenize and emulsify for 2-4 hours to fully disperse the filler into the resin solution;

[0023] S3. Finally, add the curing agent and catalyst, and stir in a cycle for 2-3 hours to obtain the adhesive solution.

[0024] The method for manufacturing a halogen-free high Tg copper-clad laminate using the adhesive comprises the following steps:

[0025] 1. The glue is impregnated on the electronic grade glass fiber cloth through a vertical glue applicator and then baked at a high temperature of 100-200°C for 8-15 minutes to form a continuous prepreg;

[0026] 2. The upper and lower surfaces of the obtained semi-cured sheet are covered with copper foil, and hot-pressed by a hot press to obtain a halogen-free high Tg copper-clad laminate with high heat resistance.

[0027] The adhesive of the present invention can effectively improve the heat resistance and toughness of the material by adding polyurethane modified epoxy resin, so that the material performance can adapt to the complex and demanding PCB lead-free process requirements; at the same time, mixed modified resins such as phosphorus-containing modified epoxy resin, modified phenolic epoxy resin, and multifunctional epoxy resin can be used to better improve the glass transition temperature, flame retardant properties, and mechanical properties of the material; adding inorganic fillers can further improve the heat shock resistance and thermal expansion coefficient of the material. BRIEF DESCRIPTION OF THE DRAWINGS

[0028] In order to more clearly illustrate the technical solution of the present invention, the following briefly introduces the drawings required for use in the present invention. Obviously, the drawings described below are only some embodiments of the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying creative work.

[0029] Figure 1 It is a flow chart of an embodiment of a method for preparing glue solution of the present invention. DETAILED DESCRIPTION

[0030] The following will be combined with the drawings in the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0031] The words "first", "second" and similar terms used in this application do not indicate any order, quantity or importance, but are only used to distinguish different components. Words such as "include" or "comprises" and similar terms mean that the elements or objects appearing before the word include the elements or objects listed after the word and their equivalents, without excluding other elements or objects. Words such as "connect" or "connected" and similar terms are not limited to physical or mechanical connections, but may include electrical connections, whether direct or indirect. "Up", "down", "left", "right", "front", "back" and the like are only used to indicate relative position relationships. When the absolute position of the object being described changes, the relative position relationship may also change accordingly.

[0032] It should be noted that, in the absence of conflict, the embodiments of the present invention and the features in the embodiments may be combined with each other.

[0033] Embodiment 1

[0034] A glue solution comprises the following components in parts by weight: 30-50 parts of polyurethane modified epoxy resin, 40-100 parts of benzoxazine resin, 60-90 parts of phosphorus-containing epoxy resin, 30-50 parts of modified phenolic epoxy resin, 30-50 parts of multifunctional epoxy resin, 30-60 parts of inorganic filler, 5-10 parts of curing agent, 0.5-5 parts of catalyst, 3-8 parts of auxiliary agent and 50-80 parts of organic solvent.

[0035] Preferably, the glue contains the following components in parts by weight: 30-50 parts of polyurethane modified epoxy resin, 50-80 parts of benzoxazine resin, 60-80 parts of phosphorus modified epoxy resin, 30-50 parts of modified phenolic epoxy resin, 30-50 parts of multifunctional epoxy resin, 30-60 parts of inorganic filler, 5-10 parts of curing agent, 0.5-5 parts of catalyst, 3-8 parts of auxiliary agent and 50-80 parts of organic solvent.

[0036] Experimental Example 1, the glue contains the following components in parts by weight: 30 parts of polyurethane modified epoxy resin, 70 parts of benzoxazine resin, 60 parts of phosphorus modified epoxy resin, 45 parts of modified phenolic epoxy resin, 30 parts of multifunctional epoxy resin, 55 parts of inorganic filler, 8 parts of curing agent, 1.5 parts of catalyst, 3 parts of auxiliary agent and 60 parts of organic solvent.

[0037] Experimental Example 2, the glue contains the following components in parts by weight: 40 parts of polyurethane modified epoxy resin, 65 parts of benzoxazine resin, 65 parts of phosphorus modified epoxy resin, 30 parts of modified phenolic epoxy resin, 35 parts of multifunctional epoxy resin, 40 parts of inorganic filler, 8 parts of curing agent, 0.9 parts of catalyst, 4 parts of auxiliary agent and 70 parts of organic solvent.

[0038] Experimental Example 3, the glue contains the following components in parts by weight: 45 parts of polyurethane modified epoxy resin, 55 parts of benzoxazine resin, 60 parts of phosphorus modified epoxy resin, 40 parts of modified phenolic epoxy resin, 30 parts of multifunctional epoxy resin, 55 parts of inorganic filler, 7 parts of curing agent, 1.2 parts of catalyst, 5 parts of auxiliary agent and 65 parts of organic solvent.

[0039] An existing glue solution contains the following components in parts by weight: 70 parts of benzoxazine resin, 50 parts of phosphorus-modified epoxy resin, 45 parts of modified phenolic epoxy resin, 35 parts of multifunctional epoxy resin, 40 parts of inorganic filler, 5 parts of curing agent, 0.8 parts of catalyst, 5 parts of auxiliary agent and 60 parts of organic solvent.

[0040] The performance comparison between the above three experimental examples and the existing glue solution is shown in the following table:

[0041]

[0042] The glue of Example 1 can effectively improve the heat resistance and toughness of the material by adding polyurethane modified epoxy resin, so that the material performance can adapt to the complex and demanding PCB lead-free process requirements; at the same time, mixed modified resins such as phosphorus-containing modified epoxy resin, modified phenolic epoxy resin, and multifunctional epoxy resin can better improve the glass transition temperature, flame retardant properties, and mechanical properties of the material; adding inorganic fillers can further improve the heat shock resistance and thermal expansion coefficient of the material.

[0043] Embodiment 2

[0044] Based on the glue of Example 1, the organic solvent is a mixture of any one or more of DMF, acetone, butanone, methyl butanone, cyclohexanone, propylene glycol methyl ether, toluene, xylene, ethylene glycol methyl ether, ethylene glycol ethyl ether, ethylene glycol butyl ether, methanol, isopropanol, propylene oxide, and cyclohexane.

[0045] Preferably, the modified benzoxazine resin is a mixture of any one or more of phenylmethane modified benzoxazine resin, double bond modified benzoxazine resin and bisphenol A type epoxy modified benzoxazine resin.

[0046] Preferably, the phosphorus-containing epoxy resin is a mixture of any one or more of DOPO-type modified epoxy resin, DOPO-HQ-type modified epoxy resin, DOPO-NQ-type modified epoxy resin, etc.

[0047] Preferably, the modified novolac epoxy resin is a mixture of any one or more of bisphenol A novolac epoxy resin, o-cresol novolac epoxy resin, and BPA novolac epoxy resin.

[0048] Preferably, the multifunctional epoxy resin is a mixture of any one or more of a trifunctional epoxy resin and a tetrafunctional epoxy resin.

[0049] Preferably, the inorganic filler is a mixture of two or more of silicon micropowder, aluminum oxide, zinc oxide, magnesium hydroxide, aluminum hydroxide, barium sulfate, silicon nitride, boron nitride and talc.

[0050] Preferably, the auxiliary agent is a mixture of any one or more of an organic silane coupling agent, a titanate ester, and an aluminate ester coupling agent.

[0051] Preferably, the curing agent is a mixture of any one or more of 4,4'-dioxydiphenyl sulfone, dicyandiamide, and phosphorus-containing phenolic curing agent.

[0052] Preferably, the catalyst is a mixture of any one or more of imidazole, 2-methylimidazole, 2-ethylimidazole, 2-phenylimidazole, 2-ethyl-4-methylimidazole, 2-ethyl-4-phenylimidazole and boric acid.

[0053] Embodiment 3

[0054] The method for preparing the glue solution of embodiment 1 or 2 comprises the following steps:

[0055] S1. Stir an organic solvent, a polyurethane-modified epoxy resin, a benzoxazine resin, a phosphorus-modified epoxy resin, a modified phenolic epoxy resin and a multifunctional epoxy resin for 2-3 hours until the epoxy resin is completely dissolved in the organic solvent;

[0056] S2. Add inorganic fillers and additives, and pass through a homogenizer to homogenize and emulsify for 2-4 hours to fully disperse the filler into the resin solution;

[0057] S3. Finally, add the curing agent and catalyst, and stir in a cycle for 2-3 hours to obtain the adhesive solution.

[0058] Embodiment 4

[0059] The method for manufacturing a halogen-free high Tg copper-clad laminate using the adhesive solution of embodiment 1 or 2 comprises the following steps:

[0060] 1. The glue is impregnated on the electronic grade glass fiber cloth through a vertical glue applicator and then baked at a high temperature of 100-200°C for 8-15 minutes to form a continuous prepreg;

[0061] 2. The upper and lower surfaces of the obtained semi-cured sheet are covered with copper foil, and hot-pressed by a hot press to obtain a halogen-free high Tg copper-clad laminate with high heat resistance.

[0062] The halogen-free high Tg copper clad laminate manufactured by the method of Example 4 has a material Tg ≥ 170°C, excellent copper foil peel strength, low CTE value, excellent dimensional stability, excellent CAF resistance, UV Blocking and AOI compatibility, low water absorption, and is suitable for the process requirements of PCB lead-free process. The product meets the technical indicator requirements of IPC specifications and can be used in consumer electronics, instrumentation, communication equipment, automotive electronics and other fields.

[0063] The above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. Any modifications, equivalent substitutions, improvements, etc. made within the spirit and principles of the present invention should be included in the scope of protection of the present invention.

Claims

1. A glue solution, characterized in that: The invention comprises the following components in parts by weight: 30-50 parts of polyurethane modified epoxy resin, 40-100 parts of benzoxazine resin, 60-90 parts of phosphorus-containing epoxy resin, 30-50 parts of modified phenolic epoxy resin, 30-50 parts of multifunctional epoxy resin, 30-60 parts of inorganic filler, 5-10 parts of curing agent, 0.5-5 parts of catalyst, 3-8 parts of auxiliary agent and 50-80 parts of organic solvent.

2. The glue according to claim 1, characterized in that: The glue contains the following components in parts by weight: 30-50 parts of polyurethane modified epoxy resin, 50-80 parts of benzoxazine resin, 60-80 parts of phosphorus modified epoxy resin, 30-50 parts of modified phenolic epoxy resin, 30-50 parts of multifunctional epoxy resin, 30-60 parts of inorganic filler, 5-10 parts of curing agent, 0.5-5 parts of catalyst, 3-8 parts of auxiliary agent and 50-80 parts of organic solvent.

3. The glue according to claim 1, characterized in that: The adhesive comprises the following components in parts by weight: 30 parts of polyurethane modified epoxy resin, 70 parts of benzoxazine resin, 60 parts of phosphorus modified epoxy resin, 45 parts of modified phenolic epoxy resin, 30 parts of multifunctional epoxy resin, 55 parts of inorganic filler, 8 parts of curing agent, 1.5 parts of catalyst, 3 parts of auxiliary agent and 60 parts of organic solvent.

4. The glue according to claim 1, characterized in that: The adhesive comprises the following components in parts by weight: 40 parts of polyurethane modified epoxy resin, 65 parts of benzoxazine resin, 65 parts of phosphorus modified epoxy resin, 30 parts of modified phenolic epoxy resin, 35 parts of multifunctional epoxy resin, 40 parts of inorganic filler, 8 parts of curing agent, 0.9 parts of catalyst, 4 parts of auxiliary agent and 70 parts of organic solvent.

5. The glue according to claim 1, characterized in that: The adhesive comprises the following components in parts by weight: 45 parts of polyurethane modified epoxy resin, 55 parts of benzoxazine resin, 60 parts of phosphorus modified epoxy resin, 40 parts of modified phenolic epoxy resin, 30 parts of multifunctional epoxy resin, 55 parts of inorganic filler, 7 parts of curing agent, 1.2 parts of catalyst, 5 parts of auxiliary agent and 65 parts of organic solvent.

6. The glue according to claim 1, characterized in that: The organic solvent is a mixture of any one or more of DMF, acetone, butanone, methyl butanone, cyclohexanone, propylene glycol methyl ether, toluene, xylene, ethylene glycol methyl ether, ethylene glycol ethyl ether, ethylene glycol butyl ether, methanol, isopropanol, propylene oxide, and cyclohexane; The modified benzoxazine resin is a mixture of any one or more of phenylmethane modified benzoxazine resin, double bond modified benzoxazine resin, and bisphenol A type epoxy modified benzoxazine resin; The phosphorus-containing epoxy resin is a mixture of any one or more of DOPO-type modified epoxy resin, DOPO-HQ-type modified epoxy resin, DOPO-NQ-type modified epoxy resin, etc.; The modified novolac epoxy resin is a mixture of any one or more of bisphenol A novolac epoxy resin, o-cresol novolac epoxy resin, and BPA novolac epoxy resin; The multifunctional epoxy resin is a mixture of any one or more of a trifunctional epoxy resin and a tetrafunctional epoxy resin; The inorganic filler is a mixture of two or more of silicon micropowder, aluminum oxide, zinc oxide, magnesium hydroxide, aluminum hydroxide, barium sulfate, silicon nitride, boron nitride, and talc; The auxiliary agent is a mixture of any one or more of an organic silane coupling agent, a titanate ester, and an aluminate coupling agent; The curing agent is a mixture of any one or more of 4,4'-dioxydiphenyl sulfone, dicyandiamide, and phosphorus-containing phenolic curing agent; The catalyst is a mixture of any one or more of imidazole, 2-methylimidazole, 2-ethylimidazole, 2-phenylimidazole, 2-ethyl-4-methylimidazole, 2-ethyl-4-phenylimidazole and boric acid.

7. The method for preparing the glue according to any one of claims 1 to 6, comprising the following steps: S1. Stir an organic solvent, a polyurethane-modified epoxy resin, a benzoxazine resin, a phosphorus-modified epoxy resin, a modified phenolic epoxy resin and a multifunctional epoxy resin for 2-3 hours until the epoxy resin is completely dissolved in the organic solvent; S2. Add inorganic fillers and additives, and pass through a homogenizer to homogenize and emulsify for 2-4 hours to fully disperse the filler into the resin solution; S3. Finally, add the curing agent and catalyst, and stir in a cycle for 2-3 hours to obtain the adhesive solution.

8. A method for manufacturing a halogen-free high Tg copper-clad laminate using the glue solution according to claim 1, comprising the following steps:

1. The glue is impregnated on the electronic grade glass fiber cloth through a vertical glue applicator and then baked at a high temperature of 100-200°C for 8-15 minutes to form a continuous prepreg; 2. The upper and lower surfaces of the obtained semi-cured sheet are covered with copper foil, and hot-pressed by a hot press to obtain a halogen-free high Tg copper-clad laminate with high heat resistance.

Citation Information

Patent Citations

  • High-heat-resistance medium-Tg copper-clad plate and preparation method thereof

    CN113912981A

  • Low-halogen flame-retardant resin and preparation method thereof

    CN114907669A

  • Adhesive suitable for HDI copper-clad plate as well as preparation method and application of adhesive

    CN116445113A

  • Preparation method of halogen-free low-CTE copper-clad plate

    CN117320292A

  • Polyurethane modified epoxy resin and preparation method thereof

    CN118459939A

Cited By

  • Ultrathin flame-retardant halogen-free epoxy glass fiber board and preparation method thereof

    CN122302503A